MODAL SOSIAL PEDAGANG BUAH DI PASAR PAGI ARENGKA KOTA PEKANBARU - Leni Sirait; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted on fruit traders in Arengka Morning Market in Pekanbaru City with the aim to find out how the elements of social capital and the obstacles faced by fruit traders in Arengka Morning Market in running social capital. This research uses descriptive qualitative research methods. The subjects in this study were 7 people. The technique of determining informants is by using purposive sampling technique. Purposive sampling is taking subjects by specifying specific characteristics in accordance with the objectives of the study so that it is expected to answer the research problem. In collecting data, researchers used observation, interview and documentation techniques. The theory used is the theory of social capital put forward by Putnam which consists of social networks, social norms and beliefs. The results of this study are that social capital is very important in running a business and the smooth operation of fruit in the Arengka Morning Market in Pekanbaru City, such as a network that can help to expedite their businesses. Social norms that become a benchmark and make them more directed. Trust that makes it easy for them to sell fruit. with the existence of social capital such as networks, norms and trust, fruit sellers can maintain fruit and facilitate their business because managing the business is carried out together and a sense of trust is established. the obstacles faced in running social capital with differences of opinion or problems that occur between the parties involved in running the business because there are those who are disappointed and disadvantaged, the cooperation will not run well and can be broken relations.